Extratos brutos de barbatimão e pacari na dieta como melhoradores de desempenho para frangos de corte - Santana, Raquel Oliveira (2013)
The present study was conducted in order to evaluate the effect of supplementation with barbatimão and pacari herbal extracts in the feed of broilers on performance, morphology of digestive organs and metabolization of nutrients in the ration. The experiment was conducted at the avian experimental facilites of the Federal University of Goiás, Brazil. Barbatimão and pacari herbal extracts were produced by percolation of hydroalcoholic solvent to 80% at the Research Laboratory of Natural Products of the Pharmacy Faculty of Universidade Federal de Goiás and showed, respectively, the content of 38.9% and 34.38% of total tannins. We employed a randomized block experimental design with nine treatments and five replications. We used 450 broiler chicks of Cobb commercial strain with average initial weight of 40g. The birds were allotted in galvanized wire metabolic cages, numbering 10 birds/cage for the pre-starter and starter stage and four birds/cage for the growth stage. Feed intake and birds weight were monitored weekly by weighing on the 1, 7, 14, 21, 28 and 35 days of the experiment. Performance characteristics evaluated were mean final weight, weight gain, feed intake and feed conversion. We conducted the metabolism trial by the total excreta collection in the periods from 17 to 21 and 30 to 34 days. We determined the metabolization coefficient of dry matter, crude protein and nitrogen balance, dry matter and nitrogen. Necropsies were performed at seven, 21 and 35 days of life of birds, for evaluation and histomorphometric indices bio. Data were subjected to analysis of variance and compared by Tukey test at 5% probability. We found that the crude Stryphnodendron adstringens had an effect on feed conversion at 21 days and increased metabolism of some nutrients in the ration. Supplementation with 400 and 600 mg/kg increased the villous height and villous /crypt in the duodenum and jejunum. The use of crude barbatimão extract at doses of 200 and 400 mg/kg is an alternative to the use of antibiotic growth promoter. We found that diets containing crude pacari extract promoted performance similarly to diets containing antibiotic performance improver. The addition of 600 mg / kg pacari extract resulted in increased villous height, crypt depth and less consequent greater villus/crypt suggesting greater capacity for nutrients absorption. Supplementation with 600 mg/kg of crude pacari extract is effective as an additive to improve performance in broilers feed.